The Iconography of Epidemics through Banksy in the Year of the Rat of the Chinese Calendar - Pérez-Rufí, María Isabel; Pérez-Rufí, José Patricio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The main premise of this paper is based on the idea that Banksy adopts a historical iconography in the representation of the disease, adapted in language and format to the contemporary context of artistic production. Our aim is the observation and description of the evolution of an artistic theme with a certain iconography. This iconography is changing and adaptable to its historical context. We apply a critical analysis based on the consult of bibliographic references. The results conclude that the pandemic by Covid-19 finds in Banksy a paradigmatic creator of media art, or mediatized, connected to digitization of cultural production.